Triple synchronous primary cancers comprising large cell neuroendocrine carcinoma of the lower uterine segment and endometrioid carcinomas of the uterine corpus and the right ovary-a rare combination: A case report - Kaichiro Yamamoto; Shin-ichi Nakatsuka; Tomochika Goto; Reiko Samoto; Aki Minami; Masatoshi Imamura (Gynecologic Oncology Reports)
We report a rare case of triple primary cancers in a 52-year-old woman who presented with abdominal pain and fever. Diagnostic imaging and subsequent histopathological evaluation revealed independent primary endometrioid carcinomas of the ovary and uterine corpus proper (UC), as well as large cell neuroendocrine carcinoma (LCNEC) originating from the lower uterine segment (LUS). Surgical resection was performed, followed by adjuvant chemotherapy (irinotecan and cisplatin). The patient demonstrated no recurrence at the 10-month follow-up.This case highlights the importance of accurate pathological differentiation, as prognosis and treatment depend on distinguishing independent primary tumors from metastatic lesions. This rare case of triple synchronous malignancies emphasizes the need for a multidisciplinary approach to ensure precise diagnosis and optimal management. Comprehensive molecular studies and advanced imaging techniques may further improve outcomes in such complex cases.